Nature's way a complete guide to health through yoga & herbal remedies - Jagadish, K. R. I. (Times books international, 1999)
A comprehensive guide on how to improve health and vitality holistically through Ayurveda, yoga and healing principles. Includes recommendations for food and juice therapies, herbal treatments and Yogasanas (yoga postures). Outlines herbal and diet remedies to treat over 200 common ailments. A complete reference work, include yoga postures and breathing exercises for beginners, intermediate learners and advanced learners of yoga. Instructions and photographs for over 150 yoga poses, as well as breathing exercises and meditation techniques.